2016
DOI: 10.1161/strokeaha.115.010600
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Vasomotor Symptoms and Carotid Intima Media Thickness in the Study of Women’s Health Across the Nation

Abstract: Background and Purpose Emerging work has linked menopausal vasomotor symptoms (VMS) to subclinical cardiovascular disease (CVD) among women. However, VMS are dynamic over time. No studies have considered how temporal patterns of VMS may relate to subclinical CVD. We tested how temporal patterns of VMS assessed over 13 years were related to carotid intima media thickness (IMT) among midlife women. Methods The Study of Women’s Health Across the Nation is a longitudinal cohort study of midlife women. 811 Caucas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 31 publications
1
36
0
1
Order By: Relevance
“…In the Penn Ovarian Aging Study over 30% of women reported having VMS at study entry, in their late reproductive years when they were still cycling regularly. 3 In the Study of Women’s Health Across the Nation (SWAN), VMS trajectories constructed from VMS assessed prospectively over 13 years of the menopause transition were examined in relation to subclinical CVD, 17 finding similar to the present results, that it was women with early onset VMS who had the highest subclinical CVD. Conversely, in the WHI observational study, it was the women with later onset VMS (reported at entry) who showed the highest risk.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In the Penn Ovarian Aging Study over 30% of women reported having VMS at study entry, in their late reproductive years when they were still cycling regularly. 3 In the Study of Women’s Health Across the Nation (SWAN), VMS trajectories constructed from VMS assessed prospectively over 13 years of the menopause transition were examined in relation to subclinical CVD, 17 finding similar to the present results, that it was women with early onset VMS who had the highest subclinical CVD. Conversely, in the WHI observational study, it was the women with later onset VMS (reported at entry) who showed the highest risk.…”
Section: Discussionsupporting
confidence: 71%
“…The few studies examining clinical CVD events yield mixed and inconclusive findings. 14-16 Further, emerging data indicate that associations between VMS and CVD risk may depend on the age at which VMS occur, 15,17 yet an age-dependence of VMS-CVD risk associations is not routinely examined. Thus, there is an important gap in knowledge about age-dependent relationships between VMS and adverse CVD events.…”
Section: Introductionmentioning
confidence: 99%
“…39 In other studies, the pattern of VMS has been shown to be associated with the risk of cardiovascular events in post-menopausal women. 40 VMS patterns may be related to a variety of relevant clinical outcomes.…”
Section: Discussionmentioning
confidence: 89%
“…The timing of hot flashes can vary dramatically across women, with some indication that early-occurring hot flashes may be those most relevant to CVD risk. 14, 21 Similar to relations between a range of female reproductive factors (e.g., hormone therapy, hot flashes) and markers of CVD risk in women, 21, 22 any modifying role of chronologic or ovarian aging in these associations requires careful consideration.…”
Section: Introductionmentioning
confidence: 99%